Poezja Wadima Andrejewa i Daniiła Andrejewa: problem przedstawienia tożsamości narodowej - Daszewskaja, Olga (Studia Rossica Posnaniensia, 2011)
The report presents an analysis of works of а Russian mystic poet and philosopher Daniel Andreev (1906–1959) and а European poet Vadim Andreev (1902–1976) as а phenomenon of 20th century's cultural development. Cross-cultural communication in the poets' works is combined with developed national identity. Vadim Andreev's poetry embodies national identity through developmeпt of motives representative for the Russian literature. Reconstituted world of the Russian literature (А. Pushkin, А. Blok, O. Mandelstam) defines axiological unity of his poetry and is of primary importance information of his creative competence